2008
DOI: 10.1097/sla.0b013e318180a3a7
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Informed Consent of Surgical Patients Using a Multimedia-Based Program?

Abstract: Use of the multimedia-based program was positively evaluated by patients, and significantly improved patients' perceived understanding of their disease and its treatment. It is, therefore, valuable in the informed consent process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…As a study by Bollschweiler et al (2008) demonstrated, adding a multimedia-based information system prior to cholecystectomy significantly increased patient perceived understanding of pathophysiology and the planned procedure. 27 In this aspect it is clear that in the survey setting, the respondents’ perception of the different considerations was limited at best. In addition, our respondents were primarily college educated Caucasians, and we would recommend that future studies include a more heterogeneous population.…”
Section: Discussionmentioning
confidence: 99%
“…As a study by Bollschweiler et al (2008) demonstrated, adding a multimedia-based information system prior to cholecystectomy significantly increased patient perceived understanding of pathophysiology and the planned procedure. 27 In this aspect it is clear that in the survey setting, the respondents’ perception of the different considerations was limited at best. In addition, our respondents were primarily college educated Caucasians, and we would recommend that future studies include a more heterogeneous population.…”
Section: Discussionmentioning
confidence: 99%
“…The results correlate with research performed in other countries. Some previous studies revealed that providing the patient with audiovisual information is effective in giving the patient knowledge and understanding before signing the statement of informed consent [4,5] in many different kinds of surgeries such as; laparoscopic cholecystectomies [6,7], gastric banding, knee arthroscopies, and central venous catheterizations. These studies found that the use of multimedia help the patient to gain a better understanding of the disease process and the surgical proce-dure, without experiencing any more anxiety that those not receiving the information materials [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The more interactive information is provided, the more a patient remembers (Table 1) [11, 13, 24, 34, 40, 42, 5876]. Nonetheless, the amount of information that is transferred during a preoperative consultation in an outpatient environment can be overwhelming [41].…”
Section: Future Improvements Of Surgical Informed Consentmentioning
confidence: 99%